Purification and characterization of beta-fructosidase with inulinase activity from Aspergillus niger-245 - Cruz, V. D.; Belote, J. G.; Dorta, C.; Santos, Lucinéia dos [UNESP]; Andriolo, C. R.; Khenayfes, M. D.; Cruz, R. (Inst Tecnologia Parana, 1998)
Aspergillus niger - 245 a strain isolated from soil samples showed good beta -fructosidase activity when inoculated in medium formulated with dahlia extract tubers. The enzyme was purified by precipitation in ammonium sulphate and percolated in DEAE-Sephadex A-50 and CM-cellulose columns, witch showed a single peack in all the purification steps, maintaining the I/S ratio between 0.32 to, 0.39. Optimum pH for inulinase activity (I) was between 4.0 - 4.5 and for invertase activity (S) between 2.5 and 50. The optimum temperature was 60 degrees .C for both activities and no loss in activity was observed when it was maintained at this temperature for 30 min. The K-m value was 1.44 and 5.0 respectively, for I and S and V-m value 10.48 and 30.55 respectively. The I activity was strongly inhibited by Hg2+ and Ag+ and 2 x 10(-3) M of glucose, but not by fructose at the same concentration. The enzyme showed an exo-action mechanism acting on the inulin of different origins. In assay conditions total hydrolysis of all the frutans was obtained although it has shown larger activity on the chicory inulin than that one from artichoke Jerusalem and dahlia, in the first 30 min. The obtained results suggested that the enzyme presented good potential for industrial application in the preparing the fructose syrups.
Keywords: inulinase; invertase; beta-fructosidase; inulin; fructose syrup; Aspergillus niger